Draught animal power for climate-smart farming in semi-arid and arid Nigeria: Challenges and oppourtunities: Climate Smart Farming in Nigeria - Sikiru, Akeem B; Makinde, Olayinka John; Ambali, Munirat I; Muhammad, Ibrahim R.; Egena, Stephen Sunday Acheneje; Olatunbosun, Rasheed Babatunde (Annals of Arid Zone, 2023)
This paper examines the challenges faced by farmers in the Sudano-Sahelian ecological zone of Nigeria, which is characterized by a semi-arid to arid climate with limited rainfall and high temperatures. The paper highlights the importance of the region for agriculture, particularly for crops such as millet, sorghum, cowpea, groundnut and maize, but also highlights the challenges faced by the farmers, including climate variability and soil degradation. The paper argues that climate-smart agriculture (CSA) practices, such as use of draught animal power (DAP), conservation agriculture, integration of trees and crops, harvesting water and integrated pest management, can address these challenges. The paper focuses on the use of DAP as a means of supporting agricultural practices in the region. The use of DAP is an important source of power for farmers, particularly those who cannot afford to buy or maintain tractors or other machinery. The paper argues that the use of DAP can increase agricultural productivity, reduce labor costs, and improve farmers’ income, contributing to poverty reduction in the region. Additionally, the use of DAP can reduce greenhouse gas emissions, making it a more environmental friendly option than the tractors. The paper suggests that future research on DAP should explore the social and emotional bonds existing between humans and their working animals, as well as the cultural and societal values attached to working animals in different parts of the region. Research could also focus on how modern technology, such as GPS tracking and other monitoring devices, can improve the welfare of draught animals and enhance their productivity. By using these tools to track animal health and performance, farmers and other animal handlers can more effectively identify and address potential issues before they become serious problems. In conclusion, the use of DAP has the potential to solve some of the challenges faced by farmers in the Sudano-Sahelian ecological zone of Nigeria and promote climate-resilient agricultural practices in the region. Further research is needed to explore the human-animal relationship and sustainable, humane use of draught animals, as well as the cultural and societal values attached to working animals in different parts of the world.